Clipping dalam Pembentukan Kata Bahasa Melayu Manado - Lengkey, Maxi C.M (Kajian Linguistik, 2015)
The aim of thiswriting is to describeManado Malay Word Formation with non morphologicalprocesses as affixation,Reduplication and Compounding but, to discusswordformation trough creation processes ,where, clipping, blending and borrowingwords are items to be used within.                                               Keywords: Proses non morfologis, clipping, blending, borrowing words.